La contribución del cooperativismo agrario al desarrollo territorial: hallazgos a partir de casos en Chile y Uruguay - Adrián Rodríguez-Miranda; Sofía Boza; Aracely Núñez (Revista Iberoamericana de Estudios de Desarrollo)
Agricultural cooperatives are a deeply rooted phenomenon in Latin America, while territorial development is increasingly present in public policies and in communities’ strategies. This article aims to analyze the practices and visions of the members of two agricultural cooperatives in Chile and Uruguay, on the basis of a conceptual framework drawn up, to identify the contribution of agricultural cooperatives to territorial development in four dimensions: productive, social-community, political-institutional, and participation-mobilization. The Uruguayan case shows a cooperative more committed to the development of its territory; while, in the Chilean case, the relationship with the community is more indirect and based on the approach of the «trickle-down» effect. These results must be interpreted considering the different institutional contexts and related public policies in each case. The latter opens an interesting research agenda on the relations between agricultural cooperatives, territorial development, and public policies.